2018
DOI: 10.1002/ajmg.c.31619
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding inheritance of holoprosencephaly

Abstract: Holoprosencephaly (HPE) is a complex genetic disorder of the developing forebrain characterized by high phenotypic and genetic heterogeneity. HPE was initially defined as an autosomal dominant disease, but recent research has shown that its mode of transmission is more complex. The past decade has witnessed rapid development of novel genetic technologies and significant progresses in clinical studies of HPE. In this review, we recapitulate genetic epidemiological studies of the largest European HPE cohort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 77 publications
2
56
0
1
Order By: Relevance
“…13,14 HPE also occurs in a non-syndromic form with various modes of inheritance reported, including autosomal dominant with reduced penetrance and variable expressivity, autosomal recessive and a growing evidence of oligogenic inheritance. 4,15 The two patients reported in this study were diagnosed with alobar HPE in utero by ultrasound examination. Alobar HPE, which is the most severe subtype in the HPE spectrum, is classically characterized by agenesis of the corpus callosum and olfactory bulbs, fused thalami, a midline monoventricle and complete absence of the interhemispheric fissure with or without associated craniofacial defects.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…13,14 HPE also occurs in a non-syndromic form with various modes of inheritance reported, including autosomal dominant with reduced penetrance and variable expressivity, autosomal recessive and a growing evidence of oligogenic inheritance. 4,15 The two patients reported in this study were diagnosed with alobar HPE in utero by ultrasound examination. Alobar HPE, which is the most severe subtype in the HPE spectrum, is classically characterized by agenesis of the corpus callosum and olfactory bulbs, fused thalami, a midline monoventricle and complete absence of the interhemispheric fissure with or without associated craniofacial defects.…”
Section: Discussionmentioning
confidence: 88%
“…Classically, HPE can occur in a non‐syndromic form or as part of recognizable monogenic conditions and chromosomal anomalies. To date, non‐syndromic HPE has been associated with pathogenic variants in nearly 17 genes, while syndromic HPE features in at least 25 monogenic conditions . The gene KMT2D has not been shown to play a major role in the regulation of human forebrain development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous study indicated this feline heritable brain malformation syndrome resembled a mild form of HPE [20]. Many genes have been reported to cause HPE in humans (Reviewed in [47][48][49]). However, GDF7, also known as bone morphology protein 12 (BMP12), has not been reported to be associated with HPE in humans.…”
Section: A Variant Dataset From Wgs Of Domestic Cats the 99 Lives Camentioning
confidence: 88%
“…In humans, heterogeneity in familial HPE is also identified even if different individuals are carrying the same mutation [51][52][53]. The influence of environmental or teratogenic factors or modifier genes have been suggested for the spectrum (Reviewed in [46,47,49]). Assuming no exposure to teratogen and relatively homogeneous living environment, the presence of modifier genes is suspected for the variable severity of the dilated ventricles and supratentorial cysts in cats presented here.…”
Section: A Variant Dataset From Wgs Of Domestic Cats the 99 Lives Camentioning
confidence: 99%